The Influence Of Financial Literacy, Service Features, And The Influence Of Convenience On The Decision To Use Gopay - Nurafni, Silla Septi; Rusyanti, Hesti; Astuti, Putri (Lentera Ilmu Nusantara, 2024)
This study aims to identify and analyze the influence of financial literacy, service features, and the influence of convenience on the decision to use Gopay with a case study of employees working in Cikarang. Primary data was collected through a questionnaire involving 89 respondents and quantitatively analyzed using the Smart Partial Least Square - Structural Equation Model (SMART PLS). The results of the analysis show that financial literacy, and the influence of convenience have an influence on the decision to use Gopay, while service features and service features as moderation have no influence on the decision to use Gopay. These findings make a theoretical contribution to the development of e-wallet adoption models and practical implications for fintech service providers in designing product and service development strategies. The study also highlights the importance of financial literacy education and the development of easy-to-understand features to increase e-wallet adoption in Indonesia.